Adversity Quotient Dan Work Stress Terhadap Kinerja Pegawai Dengan Komitmen Organisasi Sebagai Variabel Intervening Pada PT. Pos Indonesia (Persero) KCU Malang - Sulistyowati, Febianti Zindi; Setiani, Setiani (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2024)
This research aims to test and analyze employee performance at PT. Pos Indonesia (Persero) KCU Malang is influenced by the adversity quotient and work stress, with organizational commitment as an intervening variable. The research method is explanatory research with a quantitative approach. The sampling method uses saturated samples. Questionnaires were distributed to 83 respondents for data collection and processed using SmartPLS 4 software. The results showed that work stress and adversity quotient did not affect employee performance but did affect organizational commitment, which impacted employee performance. Meanwhile, through organizational commitment, the adversity quotient affects employee performance but does not affect work stress.Â Â